Spondyloepiphyseal dysplasia tarda: a new autosomal recessive variant with mental retardation. Issue 6 (June 1987) - Kohn, G; Elrayyes, E R; Makadmah, I; Rösler, A; Grünebaum, M
Abstract : A new variant of spondyloepiphyseal dysplasia tarda with mild to moderate mental retardation is described in three daughters born to healthy, consanguineous parents. The mode of inheritance is compatible with that of an autosomal recessive disorder. The identification of this variant is important, as it enables more precise counselling in families in which sporadic cases with this form of presentation are found.